2316. The Frequency of Multifocal Disease and Pyogenic Hip Arthritis in Neonates With Osteomyelitis. (26th November 2018) - Shin, Jiwoong; Scheuerman, Oded; Levy, Itzhak; Rubin, Lorry
Abstract: Background: Osteomyelitis and septic arthritis are important infections in neonates in intensive care units. The literature on neonatal osteoarticular infections during the past twenty years, a period during which there was an emergence of community-associated methicillin-resistant Staphylococcus aureus (MRSA), is limited. The purpose of this study was to describe a case series of neonatal osteoarticular infections during recent decades. In particular, we sought to describe the current microbiology, prevalence of multi-bone and contiguous joint involvement, and proportion of cases with pyogenic arthritis of the hip. Methods: Multi-center retrospective chart review. Cases were identified through NICU registries at 2 tertiary/quaternary children hospitals between 1993 and 2017. The diagnosis required suggestive clinical findings plus radiological findings or positive blood, joint fluid, or bone culture. Results: Thirty cases were identified. The median gestational age was 28 weeks, with 24 (80%) cases occurring in premature babies. The median age at time of diagnosis was 33.5 days (range, 11–175) days. The most common localized clinical findings were erythema (66%) and swelling (60%); the most common systemic finding was apnea (53%). Seventy percent had osteomyelitis, 27% had both bone and joint involvement, and one had septic arthritis only. Eight babies (27%) had an infection in more than one noncontiguous site. The most commonly identified bone was the femur (41%) and joint was the knee (20%) followed by hip (17%). Of the 5 babies with hip infection, two were recognized more than 48 hours after initial presentation. An ultrasound of the hip was performed on 12 babies (40%), including 4 out of the 5 who had surgical drainage of the hip. Cultures of blood, joint fluid, and bone were positive in 23, 6, and 2 babies, respectively. Methicillin-susceptible S. aureus (71%) was the most common pathogen followed by MRSA (21%). Conclusion: Neonates in a NICU with osteoarticular infection frequently have multiple sites of involvement. The hip joint is infected in a sizeable minority of babies with osteoarticular infection. In view of the importance of early diagnosis and surgical drainage of pyogenic hip arthritis, ultrasound of the hips should be considered in neonates in a NICU with osteoarticular infection at any body site. Disclosures: All authors: No reported disclosures.